2018
DOI: 10.1590/1518-8345.2102.2981
|View full text |Cite
|
Sign up to set email alerts
|

Obesity, physical activity and prediabetes in adult children of people with diabetes

Abstract: Objectives:Determine prevalence of obesity / overweight, physical activity (PA) and prediabetes in adult children of parents with type 2 diabetes; identify differences according to sociodemographic variables, and describe the relationship of obesity/overweight with fasting glucose (FG) and glycosylated hemoglobin (A1C). Methods:Cross-sectional study in 30 Mexican families with 53 participating adult children. Obesity / overweight was determined with Body Mass Index (BMI), Waist Circumference (WC) and body fat … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
5
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 14 publications
4
5
0
4
Order By: Relevance
“…The present findings emphasize the role of obesity as a major risk factor for developing prediabetes in SA. These findings are in accordance with prior reports from SA 31 and worldwide 29,30,32,46 . Lifestyle interventions, including weight reduction, lowered the risk of progression to diabetes mellitus by 58% in the Diabetes Prevention Program 47 .…”
Section: Discussionsupporting
confidence: 93%
“…The present findings emphasize the role of obesity as a major risk factor for developing prediabetes in SA. These findings are in accordance with prior reports from SA 31 and worldwide 29,30,32,46 . Lifestyle interventions, including weight reduction, lowered the risk of progression to diabetes mellitus by 58% in the Diabetes Prevention Program 47 .…”
Section: Discussionsupporting
confidence: 93%
“…Based on our results, the MET score in patients with DM was significantly less than that in the non-DM subjects, and most of them were inactive same the other studies on DM were demonstrated the majority of them has low PA [20]. BMI in the DM and non-DM subjects was the same in this investigation, although other studies showed significantly high BMI in patients with DM [20,21].…”
Section: Discussionsupporting
confidence: 76%
“…In this study, we analyzed the data of a high number of adult patients with type 2 DM to evaluate the association between the self-reported MET score and vascular diseases in patients with DM. Based on our results, the MET score in patients with DM was significantly less than that in the non-DM subjects, and most of them were inactive same the other studies on DM were demonstrated the majority of them has low PA [ 20 ]. BMI in the DM and non-DM subjects was the same in this investigation, although other studies showed significantly high BMI in patients with DM [ 20 , 21 ].…”
Section: Discussionsupporting
confidence: 63%